Integrasi Spasial dan Sosial Dalam Mewujudkan Livable Settlement di Kawasan Urban Lhokseumawe - Qanitatul Isra Qamal; AR Fuad Hasanuddin; Dina Meitriana; Abdul Razak Nawaf (Prodi Arsitektur, Fakultas Sains dan Teknologi bekerja sama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Spatial and Social Integration in Achieving Livable Settlements in Urban Lhokseumawe. Lhokseumawe City faces spatial-social disparities from urbanization in Banda Sakti and Gampong Pusong areas. This study analyzes spatial-social integration for sustainable livable settlements in 2025 using sequential explanatory mixed methods: quantitative survey (Likert scale, one-way ANOVA) followed by qualitative (interviews, FGD, participatory observation). Findings reveal Banda Sakti excels in spatial order, public facilities, and social cohesion, while Gampong Pusong suffers infrastructure deficits and social disintegration. Integrative strategies include adaptive spatial planning, community empowerment, and multi-stakeholder collaboration, contributing to policy frameworks forsustainable settlements in developing Indonesian cities.